Assessment of Adenosine deaminase specific activity in serum and saliva of patients with chronic gingivitis - Hazema Mossa Khalil; Zahraa Hussein M. Kadri; Hadeel Khlil Rahman (مجلة مركز بحوث التقنيات الاحيائية, 2014)
Adenosine deaminase (ADA) is an enzyme that catalyzes the deamination of adenosine to inosine. The enzyme is widely distributed in human tissues and work as a marker of cellular immunity, and its activity is found to be elevated in those diseases in which there is a cell-mediated immune response. The aim of this study was to explore the usefulness of ADA specific activity in serum and saliva as a biomarker of chronic gingivitis (CG). Thirty CG patients and 15 CG-free controls were enrolled in the study, and they were attendant of the Dental Clinic at the College of Dentistry Medicine (University of Baghdad) during the period January-March 2013. The results demonstrated that the ADA mean specific activity was significantly (P ≤ 0.001) increased in serum (17.58 ± 0.81 vs. 0.75 ± 0.03 U/mg protein) and saliva (85.43 ± 2.43 vs. 0.11 ± 0.03 U/mg protein) of CG patients as compared with controls. Accordingly, it is possible to conclude that ADA specific activity might be a good biomarker for CG, especially in saliva, and can reflect inflammatory and destruction processes in the periodontal tissue.